Musealización de restos arqueológicos en el Cuarto Real de Santo Domingo, Granada (España) - Gallego Roca, Javier (Restauro Archeologico, 2017)
The integration and creation of a museum to display the archeological remains of the Royal Rooms of Santo Domingo, especially in relation to the Qubba, make this building the most valuable and meaningful ‘piece’ of all the Cuatro’s contents. On this historical platform, the activities proposed for the creation of a museum outlined in the competition rules are easily and suitably organized according to established stratigraphic criteria, with the different architectural elements completing the ideas for the project: the Qubba, the XIX-century palacete (or rather, interventions from the XIX century onwards, according to documented sources which are attached), the romantic garden, and the remains. The project was conceived in a global scale with the aim of achieving the urban recuperation of this significant fragment of the city of Granada; all of this was the inspiration for our idea behind our intervention proposal with its overriding motto: open gardens